Artikulasi Teologi Sunni di Indonesia: Sejarah, Ekspresi dan Gerakannya - Achmad Muhibin Zuhri; Winarto Eka Wahyudi (Universitas Nahdlatul Ulama Surabaya, 2021)
Indonesia is the largest Muslim population in the world. As a country with diverse traditions and ethnicities, Islam in this equatorial state has also managed to co-exist in harmony with the local culture. This reality is allegedly the result of the Islamic understanding embraced by most Muslims in Indonesia. It is ahlu sunnah wal jamaah, or in the western tradition known as the Sunni. Throughout history, the Sunni sect was supported by a majority of Muslims. He is recognized as the ideology of various groups - both large and small - in multiple parts of the Islamic world.